Assessment of CE‐ICP/MS hyphenation for the study of uranyl/protein interactions. Issue 11 (14th April 2015) - Huynh, Thi‐Ngoc Suong; Bourgeois, Damien; Basset, Christian; Vidaud, Claude; Hagège, Agnès
Abstract : Identification of uranyl transport proteins is key to develop efficient detoxification approaches. Therefore, analytical approaches have to be developed to cope with the complexity of biological media and allow the analysis of metal speciation. CE‐ICP/MS was used to combine the less‐intrusive character and high separation efficiency of CE with the sensitive detection of ICP/MS. The method was based on the incubation of samples with uranyl prior to the separation. Electrophoretic buffers were compared to select a 10 mM Tris to 15 mM NaCl buffer, which enabled analyses at pH 7.4 and limited dissociation. This method was applied to the analysis of a serum. Two main fractions were observed. By comparison with synthetic mixtures of proteins, the first one was attributed to fetuin and in a lesser extent to HSA, and the second one to uranyl unbound to proteins. The analysis showed that fetuin was likely to be the main target of uranyl. CE‐ICP/MS was also used to investigate the behavior of the fetuin–uranyl complex, in the presence of carbonate, an abundant complexing agent of uranyl in blood. This method enabled association constants determination, suggesting the occurrence of both FETUA(UO2 2+ ) and FETUA(UO2 2+ )(CO3 2− ) complexes, depending on the carbonate concentration.